Origins of vocal-entangled gesture. (October 2022) - Pouw, Wim; Fuchs, Susanne
Abstract: Gestures during speaking are typically understood in a representational framework: they represent absent or distal states of affairs by means of pointing, resemblance, or symbolic replacement. However, humans also gesture along with the rhythm of speaking, which is amenable to a non-representational perspective. Such a perspective centers on the phenomenon of vocal-entangled gestures and builds on evidence showing that when an upper limb with a certain mass decelerates/accelerates sufficiently, it yields impulses on the body that cascade in various ways into the respiratory–vocal system. It entails a physical entanglement between body motions, respiration, and vocal activities. It is shown that vocal-entangled gestures are realized in infant vocal–motor babbling before any representational use of gesture develops. Similarly, an overview is given of vocal-entangled processes in non-human animals. They can frequently be found in rats, bats, birds, and a range of other species that developed even earlier in the phylogenetic tree. Thus, the origins of human gesture lie in biomechanics, emerging early in ontogeny and running deep in phylogeny. Highlights: Communicative bodily gestures are assumed to emerge late in ontogeny and phylogeny. Vocal entangled gestures are rooted in biomechanical linkages with respiration. This link is explored during vocal-motor babbling, long before other gestures develop. We show that vocal entangled gestures have deep roots in phylogenesis and are shared with other animals. Understanding vocal-entangled gestures requires an interdisciplinary biobehavioral perspective.